Comparative study of the price behavior between developed and emerging markets : how correlated they are? - Chhbra, Monish. (2008)
This paper empirically investigates the relationship between the price behaviour of emerging and developed equity markets: degree of interdependence, significant differences between volatility, under- & over-reaction, corrections and price movements.